A NIR-II light responsive hydrogel based on 2D engineered tungsten nitride nanosheets for multimode chemo/photothermal therapy. Issue 64 (22nd July 2019) - Xu, Qunfang; Zhao, Senfeng; Deng, Liu; Ouyang, Jiang; Wen, Mei; Zeng, Ke; Chen, Wansong; Zhang, Ling; Liu, You-Nian
Abstract : A hydrogel drug cargo based on 2D tungsten nitride nanosheets was fabricated. Abstract : A hydrogel drug cargo based on 2D tungsten nitride nanosheets was fabricated. It exhibits stable NIR-II responsive photothermal properties and drug release behaviour. Moreover, this hydrogel shows excellent tumour ablation efficiency in vivo via NIR-II triggered multiple chemo/photothermal therapy.